Developing a Card Game for Assessment and Intervention in the Person and the Family in Palliative Care: “Pallium Game” - Fernandes, Carla Sílvia; Vale, M. Belém; Magalhães, Bruno; Castro, João P.; Azevedo, Marta D.; Lourenço, Marisa (MDPI, 2023)
Abstract: Communication between the multidisciplinary team, the person, and the family in palliative and end-of-life situations implies, in most situations, a high negative emotional burden. Therefore, innovative strategies are needed to reduce it. The goal of this study is to describe the various stages of development and validation of a collaborative card game for people in palliative care and their families. Phase one is an exploratory study, Phase two is a Delphi study, and Phase three is a multiple case study. Participants for phases 2 and 3 were recruited using a convenience sampling method. The results demonstrate in an organized and structured way the different phases required to build a collaborative card game. The use of the game was found to be useful and effective. Four categories emerged from the content analysis of the open-ended responses: usability, evaluation tool, communication and therapeutic relationship, and meaning when using the game. A collaborative game in palliative care helps to create a space for individuals and families to express feelings and experiences, meeting the myriad of physical, psychosocial, and spiritual needs. The “Pallium game” is a useful and impactful approach to discussing sensitive topics in palliative care.
Keywords: Palliative care; Games; Terminal care; Family involvement; Patient–caregiver communication